An injectable co-assembled hydrogel blocks reactive oxygen species and inflammation cycle resisting myocardial ischemia-reperfusion injury. (1st September 2022) - Liao, Xu; Song, Xudong; Li, Jiejing; Li, Lisha; Fan, Xianglin; Qin, Qin; Zhong, Chongbin; Yang, Pingzhen; Zhan, Jie; Cai, Yanbin
Abstract: The overproduction of reactive oxygen species (ROS) and burst of inflammation following cardiac ischemia–reperfusion (I/R) are the leading causes of cardiomyocyte injury. Monotherapeutic strategies designed to enhance anti-inflammatory or anti-ROS activity explicitly for treating I/R injury have demonstrated limited success because of the complex mechanisms of ROS production and induction of inflammation. Intense oxidative stress leads to sustained injury, necrosis, and apoptosis of cardiomyocytes. The damaged and necrotic cells can release danger-associated molecular patterns (DAMPs) that can cause the aggregation of immune cells by activating Toll-like receptor 4 (TLR4). These immune cells also promote ROS production by expressing NADPH oxidase. Finally, ROS production and inflammation form a vicious cycle, and ROS and TLR4 are critical nodes of this cycle. In the present study, we designed and prepared an injectable hydrogel system of EGCG@Rh-gel by co-assembling epigallocatechin-3-gallate (EGCG) and the rhein-peptide hydrogel (Rh-gel). The co-assembled hydrogel efficiently blocked the ROS–inflammation cycle by ROS scavenging and TLR4 inhibition. Benefited by the abundant noncovalent interactions of π–π stacking and hydrogen bonding between EGCG and Rh-gel, the co-assembled hydrogel had good mechanical strength and injectable property. Following the injection EGCG@Rh-gel into the damaged region of the mice's heart after I/R, the hydrogel enabled to achieve long-term sustained release and treatment, improve cardiac function, and significantly reduce the formation of scarring. Further studies demonstrated that these beneficial outcomes arise from the reduction of ROS production, inhibition of inflammation, and induction of anti-apoptosis in cardiomyocytes. Therefore, EGCG@Rh-gel is a promising drug delivery system to block the ROS-inflammation cycle for resisting myocardial I/R injury. Statement of Significance: 1. Monotherapeutic strategies designed to enhance anti-inflammatory or anti-ROS effects for treating I/R injury have demonstrated limited success because of the complex mechanisms of ROS and inflammation. 2. ROS production and inflammation form a vicious cycle, and ROS and TLR4 are critical nodes of this cycle. 3. Here, we designed an injectable hydrogel system of EGCG@Rh-gel by co-assembling epigallocatechin-3-gallate (EGCG) and a rhein-peptide hydrogel (Rh-gel). EGCG@Rh-gel efficiently blocked the ROS–inflammation cycle by ROS scavenging and TLR4 inhibition. 4. EGCG@Rh-gel achieved long-term sustained release and treatment, improved cardiac function, and significantly reduced the formation of scarring after I/R. 5. The beneficial outcomes arise from reducing ROS production, inhibiting inflammation, and inducing anti-apoptosis in cardiomyocytes. Graphical abstract: Image, graphical abstract